William Saroyan in Connections with Tomas Wolfe - Gonchar, Natalia (Bulletin of Yerevan University B: Philology, 2021)
William Saroyan in Connections with Tomas Wolfe.  – The author of  this article observes for the first time creative (contact and typological) connections of two american writers-contemporaries, whose works are in classical fond of  XX century literature. The parallels are carried out on the basis of many adresses to both writers utterances in their texsts of different character, to american criticism on them in 1930s, i.e. the time of great attention to their works. The matter of special interest in the article is detaction of roll-call between Saroyan's short story and some episode in Wolfe's novel «You can't go home again» (1940).
Keywords: literary connections; Saroyan; Wolfe; the novel; the short story; creative purpose; autobiographical character of works; criticism; parallels